Kepuasan Kerja Karyawan Tetap di Perusahaan Perkebunan Paya Pinang: Studi Kualitatif dalam Program KKN UINSU 2026 - Lola Kesuma Pardosi; Dea Salsabila; Nazwa Habina Alwi; Syahputri Anugerah; Husna Sari Siregar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This study aims to analyze the job satisfaction of permanent employees at Paya Pinang Plantation Company in the implementation of the 2026 UINSU Community Service Program (KKN UINSU 2026). The study employed a descriptive qualitative approach to gain an in-depth understanding of employees’ experiences in carrying out their work. Data were collected through observation, interviews, and documentation conducted during field activities. The analysis focused on several aspects related to job satisfaction, including job characteristics, compensation, working environment, relationships with coworkers, relationships with supervisors, as well as factors that support and hinder employee satisfaction. The findings indicate that permanent employees’ job satisfaction is influenced by comfort in performing their duties, harmonious interpersonal relationships, a supportive work environment, and compensation considered appropriate to their job responsibilities. In addition, communication with supervisors and cooperation among employees contribute to creating a positive working atmosphere. Several obstacles were also identified, particularly those related to workload and working conditions. This study is expected to provide an overview of employees’ job satisfaction and serve as an evaluation reference for the company in continuously improving employee welfare and productivity through more responsive human resource management.